2018
DOI: 10.1016/j.electacta.2018.05.141
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid bilayers at the mercury (Hg)/water interface

Abstract: This study reports on the electrochemical characterisation of dioleoyl phospatidylcholine (DOPC) bilayer structures on a negatively polarised mercury (Hg) electrode. The bilayers are stable on the Hg surface between-1.0 and-1.3 V applied potential. The experimental approaches were:-(i) Rapid cyclic voltammetry to "fingerprint" the bilayers, (ii) Potential step experiments to record Zn2+ reduction and, (ii) Electrochemical impedance. The results show the following. Both the specific capacitance (5 microF cm-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The hysteresis between the negative-going and positive-going sweeps may be a result of slow kinetics of adsorption and desorption, particularly if there are strong intermolecular interactions. The minimum value of specific capacitance in the positive-going sweep is 6.5 μF cm –2 and in the negative sweep it is 5.7 μF cm –2 , at approximately −0.1 V. These values are similar to those measured for DPPC on Au(111) in our earlier study (8 and 5 μF cm –2 ) and DOPC bilayers on Hg (5 μF cm –2 ) . Using eq , it is possible to estimate a coverage of the surface with SM, θ: θ = C 0 C C 0 C 1 where C 0 is the capacitance of the clean surface, C 1 is the capacitance of a perfect bilayer, and C is the measured capacitance.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The hysteresis between the negative-going and positive-going sweeps may be a result of slow kinetics of adsorption and desorption, particularly if there are strong intermolecular interactions. The minimum value of specific capacitance in the positive-going sweep is 6.5 μF cm –2 and in the negative sweep it is 5.7 μF cm –2 , at approximately −0.1 V. These values are similar to those measured for DPPC on Au(111) in our earlier study (8 and 5 μF cm –2 ) and DOPC bilayers on Hg (5 μF cm –2 ) . Using eq , it is possible to estimate a coverage of the surface with SM, θ: θ = C 0 C C 0 C 1 where C 0 is the capacitance of the clean surface, C 1 is the capacitance of a perfect bilayer, and C is the measured capacitance.…”
Section: Resultssupporting
confidence: 80%
“…The minimum value of specific capacitance in the positive-going sweep is 6.5 μF cm −2 and in the negative sweep it is 5.7 μF cm −2 , at approximately −0.1 V. These values are similar to those measured for DPPC on Au(111) in our earlier study (8 and 5 μF cm −2 ) 56 and DOPC bilayers on Hg (5 μF cm −2 ). 76 Using eq 2, it is possible to estimate a coverage of the surface with SM, θ:…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Nelson and co-workers were able to correlate DOPC film thickness on Hg with capacitance to demonstrate a phase transition between a complete monolayer and a partial bilayer on Hg. 40 In another study, Lipkowski and co-workers showed with AFM data that the thickness of DMPC bilayers was lower in the potential region of lowest capacitance and concluded that the changes in capacitance with potential were mainly related to changes in overall permittivity. 51 A similar conclusion has been drawn for DMPS bilayers, which have higher capacity but similar chain tilt angle (and therefore similar bilayer thickness) to DMPE bilayers.…”
Section: Resultsmentioning
confidence: 97%
“…In the case of capacity data, the effects on capacity from film thickness and from average permittivity cannot be separated so a separate structural method is needed to confirm the interpretation of changes or differences in capacity. Nelson and co-workers were able to correlate DOPC film thickness on Hg with capacitance to demonstrate a phase transition between a complete monolayer and a partial bilayer on Hg . In another study, Lipkowski and co-workers showed with AFM data that the thickness of DMPC bilayers was lower in the potential region of lowest capacitance and concluded that the changes in capacitance with potential were mainly related to changes in overall permittivity .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation